Data from: Nuclear genetic analysis of the red fox across its trans-Pacific range ... - Sacks, Benjamin N.; Lounsberry, Zachary T.; Statham, Mark J. (Dryad, 2018)
The red fox (Vulpes vulpes) occurs on multiple continents in diverse habitats, making it an informative system for evolutionary genomic research. However, its phylogeography remains unclear. Previously, mitochondrial DNA and small numbers of nuclear loci provided discordant views. Both markers indicated deep divergence (~ 0.5 MY) between Eurasian and southern North American populations but differed in the apparent continental affinity of Alaskan red foxes, implying some degree of gene exchange during secondary contact (~0.1 MY). We assayed >173,000 nuclear genomic sites in 52 red foxes, along with 2 Rueppell’s (V. rueppellii) foxes and a gray wolf (Canis lupus) using the Illumina CanineHD BeadChip. We obtained 5,107 SNPs that were polymorphic in the foxes. Consistent with the Afro-Eurasian origins of red foxes, genetic diversity was higher in Eurasian than North American samples. Phylogenetic trees indicated that Alaskan and southern North American red foxes formed a monophyletic group nested within the ... : 4Dryad_14Sept2017SNP genotypes ...